FUNGSI DAN MAKNA AKSARA SIMBOL PADA TEKS KAJANG DALAM RITUAL NGABEN DI BALI - Suweta, I Made (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
The implementation of Hindu teachings in Bali poses a blend of the universal Hindu faith concept (Pancha Sraddha) and the indigenous wisdom. One of the indigenous elements is the use of kajang or drawing of sacred scripts on small piece of cloth used as a cover of corpse in the cremation ceremony. There are two urgent problems at issue here: (1) In what manifestation can God be glorified through kajang scripts? and (2) Why is God worshiped in the kajang scripts? The data collection in this paper is carried out by observing the data contained on the kajang scripts based on bibliographical studies and seeing in person the use of kajang in the cremation ceremony, and then analyzed them in a qualitative descriptive method. Results of the analysis undertaken are (1) Manifestation of God worshiped in the form of kajang scripts is the Supreme God, Ruler of Rwa Bhineda (basic dualism), Trinity, Shiva, the Ancestors, Devata Nawa Sanga and (2) The worship with the meaning of invocation to God consist of: invocation to attain moksha and sanctity as well as to get protection of the Gods and forgiveness.Keywords: Teks, Ngaben, Aksara, Simbol, Doa